2008
DOI: 10.1097/icl.0b013e3180515299
|View full text |Cite
|
Sign up to set email alerts
|

Changes in the Anterior and Posterior Radii of the Corneal Curvature and Anterior Chamber Depth by Orthokeratology

Abstract: Overnight orthokeratology lens wear alters the anterior corneal shape rather than the posterior radius of the corneal curvature and the anterior chamber depth. This finding suggests that the primary factor in the refractive effect of orthokeratology is change in the anterior corneal shape rather than overall corneal bending.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
34
1
3

Year Published

2010
2010
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(41 citation statements)
references
References 11 publications
3
34
1
3
Order By: Relevance
“…11,12 However, these studies did not investigate the effect of ortho-k on ASL. We found that ASL remained unchanged during 6 months of wearing ortho-k lenses compared with wearing single-vision spectacles.…”
Section: Discussionmentioning
confidence: 99%
“…11,12 However, these studies did not investigate the effect of ortho-k on ASL. We found that ASL remained unchanged during 6 months of wearing ortho-k lenses compared with wearing single-vision spectacles.…”
Section: Discussionmentioning
confidence: 99%
“…Orthokeratology renders the cornea an asymmetric nonphysiological oblate shape [7], depending on the extent of myopic correction [6,[8][9][10][11][12][13]. It also results in a decrease in corneal thickness and increase in the flattening of corneal curvature [10,[13][14][15][16][17] and might therefore be expected to lead to a decrease in NCT measurements of IOP.…”
Section: Introductionmentioning
confidence: 94%
“…Las capas anteriores de la córnea son las principales afectadas durante el tratamiento de ortoqueratología; esto se comprobó al analizar la capa anterior y posterior corneal y la profundidad de la cámara anterior a través de Pentacam, en las semanas 2, 4, 8, 12, 24, 36 y 53 (9). El cambio refractivo está directamente ligado a la alteración de la curvatura anterior corneal, por lo que no se encontraron modificaciones en la curvatura corneal posterior.…”
Section: Rangos De Curvatura Corneal En Los Que Más Se Practica La Orunclassified